Cawthon, Cowan et. al 2026 source data - Aidan Cowan (21440315) (2025)
Microbial fermentation offers a sustainable alternative to fossil-derived chemical production; however efficient, scalable bioprocesses remain limited in part by the difficulty of engineering robust production hosts. Here, we demonstrate the development of a high-titer production strain of Escherichia coli by growth coupling its production of fatty alcohols through complementation of a synthetic fermentation deficit. We implemented a reverse β-oxidation (rBOX) pathway for fatty alcohols which is bioenergetically equivalent to ethanol fermentation, enabling the growth of a strain otherwise incapable of rebalancing its redox state due to the knockout of canonical fermentation. This stable, growth-coupled phenotype enabled  adaptive evolution of the production strain, to accumulate mutations that increase rBOX flux and thereby accelerate growth over the course of iterative outgrowth. The evolved strains displayed a fourfold increase in maximum productivity, up to 110 ± 0.15  mg/L/hr, and a threefold increase in final titer up to 2.5 ± 0.28 g/L over the initially constructed strain. Proteomic analyses of evolved strains indicated differential expression of enzymes at key metabolic nodes and activation of latent genes with functions overlapping those of rBOX enzymes. These results establish redox-balanced growth coupling as a powerful tool for strain improvement and demonstrate rBOX as a practical synthetic fermentation pathway.